2011
DOI: 10.1530/erc-11-0102
|View full text |Cite|
|
Sign up to set email alerts
|

Leptin deficiency suppresses MMTV-Wnt-1 mammary tumor growth in obese mice and abrogates tumor initiating cell survival

Abstract: Obesity increases both the risk and mortality associated with many types of cancer including that of the breast. In mice, obesity increases both incidence of spontaneous tumors and burden of transplanted tumors. Our findings identify leptin, an adipose secreted cytokine, in promoting increased mammary tumor burden in obese mice and provide a link between this adipokine and cancer. Using a transplantable tumor that develops spontaneously in the Murine Mammary Tumor Virus (MMTV)-Wnt-1 transgenic mice, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 56 publications
(77 reference statements)
6
100
1
Order By: Relevance
“…Also, xenografts of MMTV-Wnt1 tumors transplanted in diet-induced obese mice grow faster as compared with lean counterparts (17). Consistent with the important role of leptin in breast tumorigenesis, xenografts of MMTV-Wnt1 cancer cells transplanted into leptin-deficient obese (Ob/Ob) mice display stunted growth (18). Cellular studies from our laboratory and others have shown that leptin signaling regulates various molecules involved in proliferation, adhesion, invasion, migration, inflammation, and angiogenesis, such as cyclin D1, survivin, ␤3 integrin, interleukin-1 (IL-1), IL-1 receptor, vascular endothelial growth factor, and its receptor type 2 in breast carcinogenesis (6, 19 -25).…”
mentioning
confidence: 79%
“…Also, xenografts of MMTV-Wnt1 tumors transplanted in diet-induced obese mice grow faster as compared with lean counterparts (17). Consistent with the important role of leptin in breast tumorigenesis, xenografts of MMTV-Wnt1 cancer cells transplanted into leptin-deficient obese (Ob/Ob) mice display stunted growth (18). Cellular studies from our laboratory and others have shown that leptin signaling regulates various molecules involved in proliferation, adhesion, invasion, migration, inflammation, and angiogenesis, such as cyclin D1, survivin, ␤3 integrin, interleukin-1 (IL-1), IL-1 receptor, vascular endothelial growth factor, and its receptor type 2 in breast carcinogenesis (6, 19 -25).…”
mentioning
confidence: 79%
“…The role of leptin in tumor growth is demonstrated via mice cancer models. More specifically, MMTV-Wnt-1 mice, a model of mammary tumor growth, that are obese but leptin deficient, have suppressed mammary tumor growth and decreased tumor cell survival compared with those that are leptin sufficient [36]. Leptin acts as a growth hormone in the MCF-7 breast cancer cell line through an increase in aromatase via ERK and STAT pathways [37], as well as enhanced DNA binding of the AP-1 transcription factor [37].…”
Section: Leptinmentioning
confidence: 99%
“…Under physiologic conditions, leptin serves an anorexigenic function. It also functions to stimulate proinflammatory pathways in monocytes and macrophages and has been shown to promote tumor growth in mammary tumor systems (7). In contrast, synthesis and secretion of adiponectin, an anti-inflammatory and proapoptotic adipokine, is often downregulated in obesity (6).…”
Section: Articles By Iyengar Et Al Published In This Issue Cancer Prmentioning
confidence: 99%